Communication regarding adverse neonatal birth events: Experiences of parents and clinicians. Issue 5 (September 2021) - Loren, Davia Liba; Lyerly, Anne Drapkin; Lipira, Lauren; Ottosen, Madelene; Namey, Emily; Benedetti, Thomas; Dunlap, Benjamin S; Thomas, Eric J; Prouty, Carolyn; Gallagher, Thomas H
Objectives: Communicating with parents about adverse birth outcomes is challenging. We sought to describe attitudes and experiences of parents and providers regarding communication about adverse newborn birth events. Methods: From 2011–2012, we conducted semi-structured in-depth interviews with parents who believed they had experienced an adverse birth-related neonatal outcome and focus groups with healthcare providers who have communicated with parents about adverse newborn birth events from three geographically diverse US academic medical centers. We conducted qualitative thematic analysis to identify key themes. Results: Parents and providers described unique communication challenges around adverse neonatal outcomes in six categories: 1) High expectations for a positive delivery experience and the view that birth is a life event, not a medical encounter; 2) Powerful emotions associated with birth, amplified when an adverse event occurs; 3) Rapid changes when expectations for a normal birth take a sudden negative turn; 4) Family involvement adding complexity to communication; 5) Multiple patients and providers complicating communication dynamics with inter-professional teams seeking to coordinate information and care; and, 6) Concerns about litigation surrounding the birth experience. Strategies to educate parents and enhance communication were identified by both parents and providers. Conclusion: Both parents and providers experience – and may suffer as a result of – communication challenges following adverse birth events affecting the newborn. Training and resources for this care environment are needed to meet parental, extended family, and provider expectations for communication when these events occur.